Characterization of the complete mitochondrial genome of Diploastrea heliopora and phylogeny of the scleractinia species which have group I introns in their COI genes - Jiaguang Xiao (Elsevier, 2021)
Mitochondrial genome DNA is a powerful marker for resolving phylogenetic relationships among scleractinian corals. Here, we decode the complete mitochondrial genome of Diploastrea heliopora (Lamarck, 1816) for the first time. The general features are 18 363 bp in length, and conventionally, with 13 protein coding genes, two ribosomal RNAs, and two transfer RNAs. Gene arrangement and distribution are similar to other scleractinian corals. Moreover, the COI gene of D. heliopora is broken up into two parts by a complex group I intron. This intron is 1076 bases in length and contains helical structures (P1-P10, except P2) and four conserved regions (P, Q, R, and S). The mitochondrial genome of D. heliopora has asymmetric base composition (13.03% C, 20.29% G, 25.91% A, and 40.77% for T). Based on concatenated protein coding genes, ML and BI trees show similar phylogenetic relationship: D. heliopora clustered closely with Sclerophyllia maxima and Echinophyllia aspera into the robust branch. The data and conclusion in this study are reference for further phylogenetic studies of corals.